Предмет: Математика,
автор: gavregavr
7(x-6) = 5(x+1) - 3(x+2)
--------- ---------
4 3
Срочно помогите! Дам 10 баллов♥️
Ответы
Автор ответа:
0
Ответ:
Пошаговое объяснение:
7(x-6) = 5(x+1) - 3(x+2)
--------- ---------
4 3
3*7(х-6)=4*5*(х+1)-3*12(х+2)
21х-126=20х+20-36х-72
21х-20х+36х=20-72+126
37х=74
х=74:37
х=2
Похожие вопросы
Предмет: Математика,
автор: oksanamatveychuk1987
Предмет: Алгебра,
автор: nnkv6by8j6
Предмет: Английский язык,
автор: qrarslan
Предмет: Физика,
автор: dashanazarova1
Предмет: Химия,
автор: ksu3415